PENGARUH PEMBERIAN AIR REBUSAN DAUN UBI JALAR (Ipomea batatas) TERHADAP PENINGKATAN JUMLAH TROMBOSIT MENCIT (Mus musculus) - Widyastuti, Rahma (Universitas Muhammadiyah Surabaya)
PENGARUH PEMBERIAN AIR REBUSAN DAUN UBI JALAR (Ipomea batatas) TERHADAP PENINGKATAN JUMLAH TROMBOSIT MENCIT (Mus musculus)Rahma Widyastuti, S.Si, M.KesAkademi Analis Kesehatan UNMUH SurabayaabstractThe leaves of sweet potato contains a very high nutritional value, so it can be used as a vegetable and as a herbal remedy. Sweet potato leaves are often found in various regions in Indonesia. This vegetable contains polyphenols that act as antioxidants that fight disease into the body. . In the leaves of sweet potato 100g contains 117 mg of calcium, 1.8 mg iron, 3.5 mg carotene, 7.2 mg vitamin C, 1.6 mg vitamin E and 0.5 mg of vitamin K, B vitamins, beta-carotene, as well as protein. Formulation of the problem of this study was to determine whether there are effects of sweet potato leaves boiled water to increase platelet counts in mice. The purpose of this study was to determine the number of platelets which water is boiled sweet potato leaves and boiled water without being sweet potato leaves in mice. This research was conducted at the Laboratory of Experimental Medicine Faculty Wijaya Kusuma Surabaya and the sample examined in the Hematology Laboratory at the Center for Health Laboratory Surabaya. The number of samples from this study there were 32 mice, 16 mice as a control group and 16 mice as the treatment group. From the results of the levels of the number of platelets in the blood samples of mice known to the average levels of platelet counts after being given water boiled sweet potato leaves as much as 210.5 / mm3 of blood and platelet count levels of mice that were not given water boiled sweet potato leaves as much as 129.7 / mm3 of blood. Statistical analyzes to test differences in the levels of T showed a platelet count between which water is boiled sweet potato leaves and boiled water without being sweet potato leaves, with a value significantly less than 0.05 (5%).Â Key word : leaves of sweet potato, the levels of the number of platelets in the blood samples